2017
DOI: 10.1016/j.jiph.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The Middle East and Eastern Europe rabies Expert Bureau (MEEREB) third meeting: Lyon-France (7–8 April, 2015)

Abstract: MEEREB is an inter-regional network of countries from North Africa, Europe, the Middle East and Central Asia that work together with the aim of improving rabies control and prevention at local, regional and global level. MEEREB members met for the third time in 2015 in France (Lyon) to review the current rabies situation within the network and to discuss the way forward the prospect of a One Health approach against rabies. Dogs were the main vector of transmission in all MEEREB countries except for Croatia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…In fact, rabies vaccination in wildlife requires specific strategies and stakeholder involvement (Freuling et al, , Hsu et al, , Müller et al, , Wallace et al, ), which are different from those applied for infected dogs (Fahrion et al, ; Lembo, ). In Iran and the Middle East, rabies has been reported in many wild carnivore species such as foxes, golden jackals, wolves and martens (Janani et al, ; Picot et al, ; Seimenis, ). Our study clearly shows that some of the lineages circulating in Iran are more often found in wildlife species (in 50% of isolates from clades A1, A2, B and C altogether; n = 86) than those of the other clades (D, E, F, G and H), which were almost exclusively isolated from dogs (96%; n = 25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, rabies vaccination in wildlife requires specific strategies and stakeholder involvement (Freuling et al, , Hsu et al, , Müller et al, , Wallace et al, ), which are different from those applied for infected dogs (Fahrion et al, ; Lembo, ). In Iran and the Middle East, rabies has been reported in many wild carnivore species such as foxes, golden jackals, wolves and martens (Janani et al, ; Picot et al, ; Seimenis, ). Our study clearly shows that some of the lineages circulating in Iran are more often found in wildlife species (in 50% of isolates from clades A1, A2, B and C altogether; n = 86) than those of the other clades (D, E, F, G and H), which were almost exclusively isolated from dogs (96%; n = 25).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, rabies vaccination in wildlife requires specific strategies and stakeholder involvement (Freuling et al, 2013, Hsu et al, 2017, Müller et al, 2015, Wallace et al, 2018, which are different from those applied for infected dogs (Fahrion et al, 2017;Lembo, 2012). In Iran and the Middle East, rabies has been reported in many wild carnivore species such as foxes, golden jackals, wolves and martens (Janani et al, 2008;Picot et al, 2017;Seimenis, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These regions plus countries of North Africa and Europe, belong to the Middle East and Eastern Europe Rabies Expert Bureau (MEEREB), an interregional rabies prevention and control network. In 2015, MEEREB has called for elimination of dog-transmitted rabies through vaccine and rabies immunoglobulin stockpiles and implementation of a One Health approach to achieve rabies eradication [16].…”
Section: Situation In Asia and Regional Initiativesmentioning
confidence: 99%